Strategies to improve jump service skills at volleyball student activity unit of Muhammadiyah University of Surakarta - Jariono, Gatot; Nurhidayat, Nurhidayat; Nugroho, Haris; Nugroho, Djoko; Amirzan, Amirzan; Budiman, Indra Adi; Fachrezzy, Fahmy; Sudarmanto, Eko; Nyatara, Sae Dikdaya (Linguistics and Culture Review, 2021)
The purpose of this study is to analyze and describe strategies to improve jump service in the student activity unit of the University of Muhammadiyah Surakarta. The population and sample in this study were students who participated in the volleyball activity unit as many as 60 people, namely 30 sons and 30 daughters, purposive sampling was used in the selection of samples. This type of research presents descriptive research using a quantitative research type approach. Data analysis techniques use descriptive statistical percentages. Descriptive analysis is the purpose of analyzing and describing the characteristics of this overall data analysis used in the SPSS program version 20.0. The conclusion of this study is a strategy to improve jump service skills in the student activity unit through physical condition training by considering the special preparatory physical condition training program, pre-competition physical condition training program, main competition physical condition training program, transition physical condition training program, and compiling an exercise program. Following the characteristics of the sport of football. However, to determine the exercise program the physical condition needs to be careful, because in this study the sample used is still very little, and the need to consider other variables in conducting further research.